Effectiveness of University Research Policy in Promoting Research Engagement among Accounting Academics in Public Universities in KwaZulu-Natal - Nzuza, Zwelihle Zwe (International Journal of African Higher Education, 2020)
Wiseman Nzuza, Lawrence Mpele Lekhanya Durban University of Technology, South Africa zwelihlen@dut.ac.za, lawrencel@dut.ac.za 1st Author: Mr Zwelihle Wiseman Nzuza is a lecturer at the Durban University of Technology in the Department of Management Accounting Email address: zwelihlen@dut.ac.za Physical and Postal Address: PO Box 1334 Durban University of Technology Durban 4001 2nd Author: Dr Lawrence Mpele Lekhanya in a senior lecturer at the Durban University of Technology in the Department of Public Management & Economics Email address: lawrencel@dut.ac.za Physical and Pos It has been frequently observed that many academics with an accounting background are not research-oriented, whereas academics from fields in science and engineering believe strongly in research. At the present moment, public universities from KwaZulu-Natal are failing to grow accounting research outputs to at least minimum requirement of 0.50 units per year per lecturer as required by the South African government. University research policy (URP) is the main tool that can be used to promote research engagements of the academic staff. Therefore, the aim of the study was to identify the effectiveness of the URP in promoting accounting academics research engagement, with specific reference to the KwaZulu-Natal public universities. This study was census, descriptive, cross-sectional and quantitative in nature. With quantitative data gathered from a sample of 82 accounting academics. Data were analysed using descriptive and inferential statistics. The IBM Statistical Package for Social Sciences (SPSS) version 25.0 was used to determine statistical results. The study found that the URP is effective in terms of promoting the engagement of accounting academics in research activities and that it is highly significant. Based on the findings, the research concludes that the URP is valuable to grow accounting research outputs beyond existing limitations. Key Words: university research policy, accounting academic staff